Malcolm Baldrige approach in university management: an importance – performance matrix analysis (IPMA) / Zulkifli Mohamed and Muhammad Saiful Anuar Yusoff - Mohamed, Zulkifli; Anuar Yusoff, Muhammad Saiful (Universiti Teknologi MARA, 2021)
Academic management is an important activity in managing a university. Failure in managing academic and student affairs can void a university credibility and program accreditation by MQA. Ineffective management approach will halt the university’s progress in achieving the academic excellence and creating Society 5.0. To overcome the issue, various approaches can be applied and one of them is the Malcolm Baldrige National Quality Award (MBNQA) approach which includes six important elements in management. Malcolm Baldridge model emphasizes Leadership role, Strategic Management, Customer Focus, Data Measurement, Human Resource Focus and Work Process in order to improve organizational performance (Result). However, there is a question on what factors should be given the priority in ensuring excellence in organizational management. Therefore, this study has been conducted in order to see what is the main factor among these six elements in MBNQA approach that is considered more important in achieving organizational goals. A sample of study have been conducted on 129 staffs in Universiti Teknologi MARA Kelantan Campus (UiTMCK). Hypothesis testing revealed that 5 out of 6 factors of management elements are having a positive relationship. While IPMA analysis shows that the Human Resource Focus is the most important factor, followed by Data Measurement, Work Process Focus and Customer Focus factors that influence the effectiveness of organization. Leadership factor gained the highest performance despite its less importance compared to other factors in IPMA analysis.